Reprezentatywność badań reprezentatywnych. Analiza wybranych problemów metodologicznych oraz praktycznych w paradygmacie całkowitego błędu pomiaru - Jabkowski, Piotr (WYDAWNICTWO NAUKOWE UNIWERSYTETU IM. ADAMA MICKIEWICZA W POZNANIU, 2015)
This monograph deals with the issue of the (non-)representativeness of research surveys and is situated within the context of methodological reflection on the quality of quantitative social research that mainly aims to identify errors related to the representativeness of a sample. The entire discussion is based on the theory of total survey error, which is widely recognized as the paradigm of quantitative research methodology. The author begins by describing the basic assumptions of this paradigm and analyzes errors that occur at different stages of the research process. The main part of this monograph focuses on four topics: (1) survey sampling frames, (2) sampling schemes, (3) errors resulting from an incomplete response rate, and (4) data weighing procedures. The main aim of this monograph was to analyze the methodological consequences of certain practical actions.
Keywords: badania surveyowe; reprezentatywność próby; błędy pomiaru